Victim or injurer: Negligence-based liability rules under role-type uncertainty, with an extension to collisions of different-sized vehicles - Jeonghyun Kim; Allan M. Feldman (Brown University, Department of Economics, 2003)
This paper modifies the standard tort model by introducing role-type uncertainty, that is, it is assumed that neither party knows in advance whether she will become the victim or the injurer when an accident occurs. When the standards of care of the two parties are assumed to be set at the socially optimal levels, only pure comparative negligence and the equal division rule guarantee efficiency, while the rules of simple negligence, contributory negligence, and comparative negligence with fixed division (other than a 50:50 split) produce the possibility of inefficient equilibria. Since the pure comparative negligence rule splits liability between negligent parties according to each party's degree of fault, it makes the accident loss division independent of one's role-type. This produces a social efficiency advantage. We also extend the model to the choice of vehicle size, as a factor determining who will be the injurer and who the victim in motor vehicle collisions. In the extension we analyze various negligence-based liability rules, and tax rules, as instruments for mitigating the vehicle size “arms race.”
Keywords: K13; D61; 330; role-type uncertainty; negligence; comparative negligence; contributory negligence; equal division rule; motor vehicle collisions; vehicle size; Haftung; Rechtsökonomik; Straßenverkehrsunfall